Incidence of Corrosion on Electric Power Losses in ACSR Cables - Cárdenas, Carlos G.; Pardo, Oscar M.; Barajas, Edward; Santos, Alfonso (TECCIENCIA, 2016)
This research performed a marine atmosphere simulation, using a saline fog chamber as a means to generate accelerated corrosion of conducting aluminum with steel reinforcement, used to construct electric power transport networks. The rate of corrosion was determined through the gravimetric method that consisted in measuring the loss of mass taking place in the sample. The experiment was conducted by taking three samples of ACSR (Aluminum with Steel Reinforcement) cable of different gauges, which received a flow of alternate current while the metal was being corroded. Through measuring equipment, electric power consumption was recorded to verify changes in the energy transported, given the exposure of the samples to corrosion. Likewise, voltage and current were measured to determine the system’s stability. Results showed that the hours of exposure of the samples in the saline fog chamber generated greater effects in galvanized steel, causing damage to its zinc layer, in contrast to aluminum that turned out to be more resistant to this type of contaminant. Also, the electric power losses registered were not significant; possibly due to the sample’s exposure and energizing times.